The infinite resource creating and leading the knowledge enterprise - Halal, William E. (Jossey-Bass, 1998)
Corporate leaders, consultants and leading authorities provide "live" examples of how businesses are managing to make the most of knowledge: the infinite resource. The book includes pieces by the CEOs of Bell Atlantic, MCI and Visa International.